Optimal pricing decisions for an omni‐channel supply chain with retail service. (2nd March 2020) - Jiang, Yuqing; Liu, Liping; Lim, Andrew
Abstract: Motivated by the emergence of dominant physical stores utilizing a buy‐online‐and‐pickup‐in‐store (BOPS) channel, we examine the interaction of such a stronger retailer and a manufacturer's strategies on the pricing and service value. The dominant retailer provides an added service value to end consumers by the traditional channel and BOPS option, which has a positive influence on the market demand. The manufacturer makes the channel selection decision between a dual channel and an omni‐channel. We formulate a retailer Stackelberg game and characterize the equilibrium pricing and service solutions under centralized and decentralized cases. Our results indicate that the service value of a physical store strongly influences the players' pricing strategies. The sensitivity analysis reveals that the total revenue of the supply chain increases with the market scale expansion coefficient of the BOPS option. Furthermore, the result suggests that offering the BOPS channel is always an effective initiative to boost supply chain performance, especially in the centralized structure.